Ascorbic Acid Metabolism in Pea Seedlings. A Comparison of d-Glucosone, l-Sorbosone, and l-Galactono-1,4-Lactone as Ascorbate Precursors - Pallanca, Jane E. (American Society of Plant Physiologists, 1999)
l-Ascorbic acid (AsA) accumulates in pea (Pisum sativum L.) seedlings during germination, with the most rapid phase of accumulation coinciding with radicle emergence. Monodehydroascorbate reductase and dehydroascorbic acid reductase were active in the embryonic axes before AsA accumulation started, whereas AsA oxidase and AsA peroxidase activities increased in parallel with AsA. Excised embryonic axes were used to investigate the osone pathway of AsA biosynthesis, in which d-glucosone and l-sorbosone are the proposed intermediates. [U-(14)C]Glucosone was incorporated into AsA and inhibited the incorporation of [U-(14)C]glucose (Glc) into AsA. A higher d-glucosone concentration (5 mm) inhibited AsA accumulation. l-Sorbosone did not affect AsA pool size but caused a small inhibition in the incorporation of [U-(14)C]Glc into AsA. Oxidase and dehydrogenase activities capable of converting Glc or Glc-6-phosphate to glucosone were not detected in embryonic axis extracts. The osones are therefore unlikely to be physiological intermediates of AsA biosynthesis. l-Galactono-1,4-lactone, recently proposed as the AsA precursor (G.L. Wheeler, M.A. Jones, N. Smirnoff [1998] Nature 393: 365–369), was readily converted to AsA by pea embryonic axes. Although l-galactono-1,4-lactone did not inhibit [(14)C]Glc incorporation into AsA, this does not mean that it is not a precursor, because competition between endogenous and exogenous pools was minimized by its very small pool size and rapid metabolism.